A survey on Koreans' preferred type of collaboration between conventional medical and traditional Korean medicine doctors. Issue 20 (21st May 2021) - Lee, Yoon Jae; Gang, Byeong-Gu; Kum, Chang Jun; Lee, Keunjae; Yoon, Young Suk; Lee, Jinho; Shin, Joon-Shik; Ha, In-Hyuk
Abstract : Abstract: Although collaborative treatment by traditional Korean medicine doctors (KMDs) and medical doctors occurs, it is mainly done by referral. As no survey of the general public's preference for the type of collaboration has ever been conducted, we aimed to investigate Koreans' preferences for a collaborative treatment type. The responders were extracted by random digit dialing and then reextracted using the proportional quota sampling method by sex and age. From July to October 2017, telephone interviews were conducted and the participant responses regarding treatment history for spinal or joint diseases, experiences with collaborative treatment, and preferred type of collaborative treatment were recorded. Of the 1008 respondents, 44.64% reported a history of treatment for spinal or joint diseases at a medical institution. The concurrent collaborative treatment system, in which both KMDs and medical doctors are present in one location participating in the treatment concurrently, was the most preferred system among the respondents. Respondents who reported experience with traditional Korean medicine hospitals were more likely to prefer a one-stop treatment approach than those who did not have experience with traditional Korean medicine hospitals (adjusted odds ratio: 1.73; 95% confidence interval: 1.12–2.68). Respondents who were familiar with collaborative treatment but did not report any personal experience with it were more likely to prefer a one-stop treatment approach than those who were not familiar with collaborative treatment (adjusted odds ratio: 1.82; 95% confidence interval: 1.37–2.44). Koreans prefer a concurrent type of collaborative treatment system by KMDs and medical doctors. Therefore, efforts and support are needed to increase the application of the concurrent type of collaborative system. Abstract : Supplemental Digital Content is available in the text